1984
DOI: 10.1063/1.333022
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic phases formed during tin implantation into iron and steels

Abstract: The surface layers of pure iron, high-carbon steel and stainless steel, ion implanted with 1 X 10 17 Sn+ cm-2 , have been characterized by means of 119Sn conversion electrons Mossbauer scattering. The intermetallic phases existent in the as-implanted samples are determined, and then the thermal decomposition of these phases are established. The phase transformations observed in the treated surfaces agree reasonably well with the phase diagrams reported in the literature for stoichiometric intermetallic phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It should be clarified that the aim is to strengthen the mechanical bond between steel and coatings through formation of an isolated layer that can prevent any possible oxidation reactions during the hot-dipping process. It was found that the presence of Sn facilitates to great extent the formation of better interlayer bonds that enhance the transfer of Al coating via steel substrate [18][19][20][21][22][23]. However, the following possible chemical reactions might be expected during tinning-dipping (Al coating) of steel substrate:…”
Section: Mechanism Of Tinning-dipping Processesmentioning
confidence: 99%
“…It should be clarified that the aim is to strengthen the mechanical bond between steel and coatings through formation of an isolated layer that can prevent any possible oxidation reactions during the hot-dipping process. It was found that the presence of Sn facilitates to great extent the formation of better interlayer bonds that enhance the transfer of Al coating via steel substrate [18][19][20][21][22][23]. However, the following possible chemical reactions might be expected during tinning-dipping (Al coating) of steel substrate:…”
Section: Mechanism Of Tinning-dipping Processesmentioning
confidence: 99%
“…Improved surface properties due to the formation of intermetallic phases, including intermetallic nanostructures, were possibly due to the implantation of metal ions in the surface layers of other metals. Reports of studies in this area have appeared for a long time [4]. ese authors reported the formation of different phases in surface layer of steels and alloy layers depending on the conditions of implantation and subsequent annealing temperature.…”
Section: Introductionmentioning
confidence: 99%